TINJAUAN LITERATUR SISTEMATIS: INTERNALISASI NILAI-NILAI FILOSOFIS PENDIDIKAN OLEH PENDIDIK SEKOLAH DASAR PADA ERA KURIKULUM MERDEKA - Fransiska Eka Tri Lestari; Yeni Karneli; Zelhendri Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This investigation intends to critically analyze how primary school educators incorporate foundational theories of educational philosophy within the operational boundaries of the Merdeka Curriculum. Adopting a Systematic Literature Review (SLR) framework, the study reviews academic literature published from 2021 to 2026 focusing on core instructional shifts, character development paradigms, and the enduring legacy of Ki Hajar Dewantara's concepts. The integrated evaluation indicates that operationalizing philosophy in class manifests through child-centered pedagogy, customizable learning environments, targeted ethical instruction, and systemic realization of the Pancasila Student Profile. Rather than performing passive instructional delivery, teachers are structurally repositioned as adaptive facilitators and professional exemplars. Ultimately, conceptual harmony between classroom strategies and ancient pedagogical principles is vital for creating inclusive, creative, and ethically grounded educational systems in contemporary elementary environments. Keywords: Systematic Literature Review, Primary Education, Merdeka Curriculum, Pedagogical Philosophy.